1998
DOI: 10.1515/jpme.1998.26.3.208
|View full text |Cite
|
Sign up to set email alerts
|

Absence of phospholipase A2 activity in genital Mycoplasma hominis

Abstract: The clinical relevance of vaginal colonization with Mycoplasma hominis (M hominis) as a cause of prematurity is doubtful. One of the possible pathways which could explain the role of M hominis in the induction of preterm labour is an increased synthesis of prostaglandins by a phospholipase A2 activity. The aim of this study was to prove whether M hominis secrets proteins with a PLA2 activity and to test whether there are strain differences in the enzyme activity between M hominis isolated from women with norma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2003
2003
2005
2005

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 7 publications
0
2
0
Order By: Relevance
“…However, after adjustments for age, education and smoking, only the age !20 was identified as an independent risk factor of M. hominis infection during pregnancy. Although the causative role of M. hominis infection in prematurity was excluded in some of the studies [28,29], another found this relation very likely [30]. According to Hillier et al [17] among women with BV, the highest risk of preterm delivery of a low birth weight infant (!2,500 g) was found among those with both vaginal bacteroides and M. hominis (OR = 2.1).…”
Section: Discussionmentioning
confidence: 99%
“…However, after adjustments for age, education and smoking, only the age !20 was identified as an independent risk factor of M. hominis infection during pregnancy. Although the causative role of M. hominis infection in prematurity was excluded in some of the studies [28,29], another found this relation very likely [30]. According to Hillier et al [17] among women with BV, the highest risk of preterm delivery of a low birth weight infant (!2,500 g) was found among those with both vaginal bacteroides and M. hominis (OR = 2.1).…”
Section: Discussionmentioning
confidence: 99%
“…However, Glass and colleagues (96) were unable to identify phospholipase activity in the serotype 3 ureaplasma strain for which the complete genome was sequenced and gave the same possible explanations as those for the apparent lack of IgA1 protease activity. Interestingly, Walther et al (328) were unable to demonstrate phospholipase activity in M. hominis and they were also unable to detect phospholipase A2 coding sequences in DNA analysis (271). These findings suggest M. hominis is not important in the initiation of premature labor through elaboration of phospholipases and stimulation of prostaglandin activity.…”
Section: Secretory Productsmentioning
confidence: 97%